Parental perceptions of weight status of their children - Sarrafzadegan, Nizal (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2013)
BACKGROUND: Understanding the knowledge, attitudes, and beliefs of parents is important for planning appropriately to control their children’s weight. We aimed to study these variables in parents of normal, underweight, overweight, and obese children. METHODS: This cross-sectional study targeted the parents of normal, underweight, overweight, and obese children, who were selected using multistage random sampling method. The parents’ knowledge, attitudes, beliefs, and behaviors about the weight status of their children, weight management, obesity, diet, lifestyle, and related psychosocial factors were evaluated using a validated questionnaire. The questionnaire, which had been validated, consisted of 12 demographic, 8 knowledge, 19 attitude and beliefs, and 25 behavior questions. Mean knowledge, attitude and beliefs, and behavior scores were compared across three subgroups of parents. Student’s independent t-test, ANOVA, and Kruskal-Wallis test were used to study the correlation between different demographic and socioeconomic factors, and the studied variables. RESULTS: 90% of parents were aware that obesity is a disease, and 92% knew that eating too much fast food would lead to obesity in children. Only 5% assumed that obese children are healthier than non-obese children. The mean scores of the three subgroups showed no significant difference in knowledge, attitude and beliefs, and behavior. Families with fathers, whose education level was higher than high school diploma, rated their children’s weight status as overweight or obese significantly less than families with fathers, whose education level was high school diploma or lower (8.5% vs. 16.5%, respectively, P = 0.014). Only 12% of parents tried to help their children lose weight at least once, and only 6% arranged sport activities for the family members. In 57% and 41% of families, the child, respectively, decided how much time was enough to watch TV, and how much chocolates and sweets to eat. 46% of children watched TV for more than 2 hours/day, and 49% of children watched TV while eating meals. The mean total score of boys’ parents was significantly lower than that of girls’ parents (P < 0.05). Families with low income, with no medical insurance, or not owning a house thought that the cost of registration in sport activities for children was too high (P < 0.03). CONCLUSION: Some parents unreasonably rated the weight status of their children as overweight/obese. It is suggested that further studies be carried out to evaluate and improve parents’ knowledge, attitudes, and behaviors regarding their children’s weight.